Analisis Nilai Tambah pada Usaha Se’i Sapi di Kota Kupang Provinsi Nusa Tenggara Timur - Fransiskus Yulius Dhewa Kadju; Budi Hartono; Bambang Ali Nugroho (Fakultas Pertanian, Universitas Timor, 2021)
The high added value of beef agro-industry has increased competition among business actors, both for marketing processed products and for obtaining raw materials. The calculation of the added value of marketing se'i cow meat in Kupang City is the main objective of this research. The research was carried out during June - July 2019. The survey method was the method used during this research. Determination of the sample in this study using purposive sampling technique with five examples of MSME respondents. The results of calculations using the Hayami Method obtained an added value of Rp. 18,804.73 for each se'i product sold.